Menyoal Akibat Hukum Atas Pembuatan Akta Jual Beli Yang Tidak Dibacakan Oleh Notaris/PPAT Di Hadapan Para Pihak - Aldi Pradana Muhammad; Rusdianto Sesung (Lembaga Pengembangan Kinerja Dosen, 2024)
This research investigates the implications of not reading out the legal consequences of a sale and purchase deed prepared by a Notary/PPAT in front of the concerned parties. It employs a descriptive approach, drawing from various literature sources such as books, research findings, journals, and articles. The study underscores the Notary/PPAT's responsibility to orally communicate the deed's content to the involved parties. Failure to do so diminishes the deed's authenticity. Although the deed remains legally valid regarding the transaction, its authenticity suffers, likening it to an underhand deed. Consequently, Notaries/PPATs who overlook this obligation may face sanctions as per the relevant ethical codes for their negligence.